2007
DOI: 10.1016/j.atmosenv.2007.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and conversion of carbonyl sulfide in a lawn soil

Abstract: Carbonyl sulfide (COS) exchange fluxes between a lawn soil and the atmosphere as well as influencing factors (temperature and water content of soil) were investigated using a static cuvette. The optimal soil temperature and water content for COS consumption were about 298 K and 12.5%, respectively. The converting products of the consumed COS in the lawn soil were researched using in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS). The peaks of gas-phase products of CO 2 and surface HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…This is in reasonable agreement with Watts (2000), but larger than the 80% of Weisenstein et al (1997). As sulfur is a key plant nutrient, the uptake of OCS by soils might be a path for sulfur supplement to vegetation, especially in remote areas (Liu et al, 2007;Yi et al, 2010). OCS can be oxidized in soils (e.g.…”
Section: Accepted Manuscriptsupporting
confidence: 71%
“…This is in reasonable agreement with Watts (2000), but larger than the 80% of Weisenstein et al (1997). As sulfur is a key plant nutrient, the uptake of OCS by soils might be a path for sulfur supplement to vegetation, especially in remote areas (Liu et al, 2007;Yi et al, 2010). OCS can be oxidized in soils (e.g.…”
Section: Accepted Manuscriptsupporting
confidence: 71%
“…In our previous work we have confirmed that surface OH is the reactive site for the heterogeneous reaction or adsorption of OCS on mineral oxides [ Liu and He , 2009; Liu et al , 2006; J. Liu et al , 2007; Y. Liu et al , 2007; Liu et al , 2009]. Kaolinite is a type of aluminum phyllosilicate mineral with the empirical formula Al 2 Si 2 O 5 (OH) 4 , indicating that there are two types of adsorption sites (Al and Si sites) for OCS on the surface of kaolinite.…”
Section: Resultsmentioning
confidence: 63%
“…[13] In our previous work we have confirmed that surface OH is the reactive site for the heterogeneous reaction or adsorption of OCS on mineral oxides Liu et al, 2006;J. Liu et al, 2007;.…”
Section: Overview Uptake Behavior Of Carbonyl Sulfide (Ocs) Onto Kaolmentioning
confidence: 75%
See 2 more Smart Citations